(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Maftuchah, Febriana L, Sulistyawati, Reswari HA, Septia ED. 2021. Morphological diversity and heritability of nine local sorghum (Sorghum bicolor) genotypes in East Java, Indonesia. Biodiversitas 22: 1310-1316. Sorghum (Sorghum bicolor L. Moench) is an essential food crop after wheat, rice, maize, and barley. It has wide adaptability to various environmental conditions, including can be grown on marginal lands, so that it is potential to be developed as cheap source of carbohydrates. The present study obtain information about the morphological diversity and heritability values ??of local sorghum genotypes that occurred in East Java Province, Indonesia. The research was conducted in Purutrejo village, Pasuruan city using nine local genotypes, namely Jombang (SG-JBG), Tuban (SG-TBN), Pasuruan (GB-PSR), Lamongan 1 (SG-LMG 1), Lamongan 2 (SG-LMG 2), Sampang 1 (SG-SPG 1), Sampang 2 (SG-SPG 2), Tulungagung 1 (SG-TLG 1) and Tulungagung 2 (SG-TLG 2). The results showed that the genotype of SG-SPG 2 produced the longest panicles, while the SG-LMG 2 had the highest seed dry weight per panicle and highest number of seeds per panicle (117.34 gram/panicle dry weight and 4581.80 seeds/panicle). The genotype of SG-TLG 2 produced the largest weight of seeds, either in fresh seed (41.43 g/1000 seeds) or dry seed (31.96 g/1000 seeds). Of the nine genotypes tested, the flowering ages ranged from 42 to 53 days after planting, and the harvest ages ranged from 70 to 91 days after planting with the fastest harvest age was achieved by SG-TLG 2 The entire value of the phenotype variety on each variable was more significant than the value of the genotype range. Heritability test results show that all experimental parameters exceed 0.5 so that it is categorized as high heritability. In general, the SG-TLG 2 genotype had the most chance to be developed, because it produced the highest seed weight, both fresh seeds (41.43 g/1000 seeds) and dry seeds (31.96 g/1000 seeds). Besides, the SG-TLG shows the fastest harvest age (70 days after planting).